Energy Efficiency in Biophilic Architecture: A Systematic Literature Review and Visual Analysis Using CiteSpace and VOSviewer - Xin Ding; Yanqiu Cui; Zhengshu Chen; Hangyue Zhang (Buildings)
The advent and application of biophilic architecture bring numerous environmental, economic, and energy-efficiency benefits, playing a crucial role in advancing low-carbon, energy-saving, healthy, comfortable, and sustainable development within the construction industry. Thanks to its many advantages—such as aesthetic enhancement, improved microclimates, and negative carbon potential—biophilic architecture has been widely adopted in building design, particularly as a response to the escalating environmental crisis. Integrating plants with various architectural forms can optimize building performance, especially by reducing operational energy consumption. This study uses knowledge mapping tools like CiteSpace 6.1.R3 and VOSviewer 1.6.19 to analyze 2309 research papers from the Web of Science (WoS) published over the past decade on the topic of “energy efficiency in biophilic architecture”. It conducts visual analyses of publication trends, collaborative networks, and key themes. The research categorizes plant–architecture integration methods, focusing on three primary areas: green roofs, vertical green systems, and green photovoltaic systems. Additionally, it reviews the ways in which biophilic architecture contributes to energy savings, the research methodologies employed, energy-saving rates, and the factors influencing these outcomes. Finally, a SWOT framework is constructed to assess the strengths, weaknesses, opportunities, and potential threats of biophilic architecture, as well as its future development prospects. The findings indicate that integrating plants with building roofs is an effective energy-saving strategy, achieving energy savings of up to 70%. Furthermore, combining biophilic elements with photovoltaic systems can enhance the efficiency of solar energy generation. This study offers valuable insights for architects and researchers in designing more energy-efficient and sustainable buildings.